"Das ist Walter": The Evolving Figure of the Archetypal Hero Embodied by Velimir Bata Živojinović in the Yugoslav War Film. Issue 2 (4th May 2022) - Radović, Mina
Abstract: Velimir Bata Živojinović boasts a body of work which traverses 350 motion pictures from Classical Yugoslav Cinema over The New Film to Contemporary Serbian Cinema, historical epic to film noir, family comedy to radical avant-garde. A legendary actor and one of the most significant personalities of Yugoslav cinema, he is best remembered as the archetypal hero of the Partisan film. This research examines the ways in which Živojinović's popular figure was constructed through the genre of the war film and the brand of Partisan film distinct to Yugoslavia. By situating Živojinović's star image in the context of his oeuvre, defining Partisan aesthetics and closely analysing three different periods in the actor's career, with respect to the films which are central in developing his image as the archetypal hero, namely Kozara (Veljko Bulajić 1962), Valter brani Sarajevo/Walter Defends Sarajevo (Hajrudin Krvavac 1972), and Lepa sela lepo gore/Pretty Village, Pretty Flame (Srđan Dragojević 1996), I demonstrate how the indestructible partisan figure embodied by Velimir Bata Živojinović was established in on-screen cinematic space, and how this figure continued to develop, transform, and evolve across films, and, finally, through off-screen public space.